Decision Support System for Alarm Rationalization using Risk Assessment Matrix - Foong, Oi Mean; Mohamad Izuddin Nordin, M. (Foundation of Computer Science, 2010)
In this paper, a Decision Support System for Alarm Rationalization using Risk Assessment Matrix (ARRAM) is proposed. When performing alarms review and classifying alarms priority, the ARRAM prototype would be used by process engineers after taking into consideration the safety impact, environmental impact and economic consequences of the hazards. The ARRAM prototype pre-determines the response time available to plant operators before the hazards occur. The objectives of this paper are two-fold: (1) To configure the alarms by using Risk Assessment Matrix and (2) To develop a prototype for classifying the alarms in oil refinery focusing on Crude Distillation Unit. The proposed ARRAM model provides a user-friendly interface for decision maker in making accurate and timely decision when rationalizing random alarms data. Preliminary results show that ARRAM is a useful tool for training new process engineers in familiarizing with alarm management system in oil refinery.